Bicycle flow dynamics on wide roads: Experiments and simulation. (April 2021) - Guo, Ning; Jiang, Rui; Wong, SC; Hao, Qing-Yi; Xue, Shu-Qi; Hu, Mao-Bin
Highlights: An improved bicycle flow model that considers centrifugal effect was developed. Single-individual experiments were conducted to investigate the centrifugal effect. We conducted multi-individual experiments on a ring-shaped track for calibration. We conducted multi-individual experiments on a playground-like track for validation. Abstract: Cycling is a popular and sustainable mode of transportation. However, few studies have examined experimental and modeling studies on bicycle flow dynamics. In particular, for wide roads, the characteristics of high-density regimes in the fundamental diagram have not been well addressed, and the emergence of stop-and-go waves has not been fully understood. This study experimentally investigated bicycle flow dynamics on wide roads, using two types of 3-m-wide track. Different riding behaviors, namely, free riding, following, and overtaking, were analyzed. The bicycle flow dynamics were found to be essentially the same on the two tracks: (i) The bicycle flow rate remained nearly constant across a wide range of densities, in marked contrast to the single-file bicycle flow, which exhibited a unimodal fundamental diagram. By studying the weight density of the radial and lateral locations of cyclists, we argue that this behavior arises from the formation of more lanes with increase in global density. The newly formed lanes prevented the flow rate from decreasing. (ii) When the density exceeded 0.5 bicycles/m 2, the flow rate began to decrease, and stop-and-go traffic emerged. Based on these behavioral observations, we propose an improved heuristic-based model to simulate bicycle flow on roads of different radii and explicitly account for the centrifugal effect of bicycles. The calibration and validation results demonstrate that the proposed model can reproduce the traffic dynamics of bicycle flow.